Lithogenic Particle Transport Trajectories on the Northwest Atlantic Margin - Hwang, Jeomshik; Blusztajn, Jurek; Giosan, Liviu; Kim, Minkyoung; Manganini, Steven J.; Montluçon, Daniel; Toole, John M.; Eglinton, Timothy I. (Journal of Geophysical Research: Oceans, 2021)
ISSN:0148-0227 ISSN:2169-9275